2018
DOI: 10.1093/ibd/izx078
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Scribes Into the Inflammatory Bowel Disease Clinic Improves Quality of Care and Physician Productivity

Abstract: The use of scribes improved the physician-patient relationship, clinical efficiency, physician productivity, bone density screening, and vaccinations for flu and pneumonia. If adopted by health systems, it may lead to significant cost savings and improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Thirty-nine studies were included, comprising greater than 562,682 patient encounters (Table E1, available online at http://www.annemergmed.com). Five studies were randomized controlled trials, [15][16][17][18][19] 23 studies were prospective nonrandomized studies, 10 studies were retrospective, [43][44][45][46][47][48][49][50][51][52] and 1 study had both prospective and retrospective components. 53 All studies were published between 2010 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-nine studies were included, comprising greater than 562,682 patient encounters (Table E1, available online at http://www.annemergmed.com). Five studies were randomized controlled trials, [15][16][17][18][19] 23 studies were prospective nonrandomized studies, 10 studies were retrospective, [43][44][45][46][47][48][49][50][51][52] and 1 study had both prospective and retrospective components. 53 All studies were published between 2010 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in the United States, [15][16][17][18]21,23,24,[26][27][28][29][30][32][33][34][35][36][37][38][39][40][41][43][44][45][46][47][48][49][50][51][52][53] with 4 conducted in Australia 19,22,25,42 and 2 performed in Canada. 20,31 Nineteen studies were conducted in EDs, 17,19,20,[22][23][24][25][26][27]31,36,38,[42]<...>…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] However, one study in the ED reported a quantitative increase in patient reported satisfaction after implementation of a scribe program, 15 as has a small study in an inflammatory bowel disease clinic. 16 Only one study by Martel et al found a small but significant decrease in patient satisfaction after scribes were introduced in multiple clinics in a safety net hospital. 17 Unfortunately, the heterogeneity between different studies' survey methods limits the conclusions that can be drawn and has prevented meta-analysis of this question 18,19 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that studies have generally found no improvement in patient reported satisfaction despite physicians reporting increased face-to-face time and better quality of interactions with scribes. 16,17,20,21 Two additional studies placed independent raters in the visit, who also reported improvements in provider-patient interactions with a scribe. 22,23 The patient-provider discrepancy could possibly be due to the benefit of improved face-to-face communication being offset by patient discomfort with room crowding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation